Hungry girl simply 6 : all-natural recipes with 6 ingredients or less - Lillien, Lisa (St. Martin's Griffin, 2019)
People everywhere are craving super-simple recipes with short ingredient lists, and Hungry Girl has come to their rescue with Hungry Girl Simply 6: All-Natural Recipes with 6 Ingredients or Less! For the first time ever, chapters are organized by main ingredient<U+2015>like CHICKEN, VEGGIES, EGGS, OATS<U+2015>making it easy to find EXACTLY what you need. Featuring familiar ingredients and just a few simple steps, these recipes put everyday smart eating BACK on the table! Featuring: 95 GLUTEN-FREE recipes; 28 SHEET-PAN recipes; 91 VEGETARIAN recipes; 27 recipes in 15 MINUTES OR LESS; 59 recipes in 30 MINUTES OR LESS; 18 NO-COOK recipes.